Non-coding RNA and n6-methyladenosine modification play crucial roles in neuropathic pain - Zhang, Kexin; Li, Pei; Jia, Yuanyuan; Liu, Ming; Jiang, Jingjing (Frontiers in Molecular Neuroscience, 2022)
After peripheral nerve injury, pain signals are transmitted from primary sensory neurons in the dorsal root ganglion (DRG) to the central nervous system. Epigenetic modification affects neuropathic pain through alterations in the gene expression in pain-related areas and glial cell activation. Recent studies have shown that non-coding RNA and n6-methyladenosine (m6A) methylation modification play pivotal regulatory roles in the occurrence and maintenance of neuropathic pain. Dysregulation of the RNA m6A level via dynamic changes in methyltransferase and demethylase after central or peripheral nerve injury commonly regulates pain-associated genes, contributing to the induction and maintenance of neuropathic pain. The dynamic process has significant implications for the development and maintenance of neuropathic pain. However, the underlying mechanisms by which non-coding RNA and m6A RNA modification regulate neuropathic pain are not well characterized. This article elucidates the multiple mechanisms of non-coding RNA and m6A methylation in the context of neuropathic pain, and summarizes its potential functions as well as recent advances.